2017
DOI: 10.1007/s00277-017-3102-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of therapeutic dosages of decitabine in treating myelodysplastic syndrome: a meta-analysis

Abstract: Decitabine is used to treat myelodysplastic syndrome (MDS). This meta-analysis evaluated the efficacy and safety of different dosing regimens of decitabine in treating intermediate and/or high-risk MDS. Medline, Cochrane, EMBASE, and Google Scholar databases were searched up to October 23, 2015. Randomized controlled trials, prospective, cohort, and case series studies were included. Fifteen studies were included with a total of 1378 patients. The decitabine 100 mg/m/course dosing regimen had a greater overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The meta-analysis revealed that the therapeutic regimen influences treatment response rate. DAC 15 mg/m 2 /8 h for 3 days every 42 days was inferior to the other regimens, which is consistent with a previous report demonstrating that it was less effective than DAC 20×5 every 28 days for all-risk MDS [ 21 ]. However, among 28-day regimens, AZA 75×7 and DAC 20×5 had the highest response rates, although a statistical analysis was not possible because of the high heterogeneity, or did not show statistically significant differences because of the limited data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The meta-analysis revealed that the therapeutic regimen influences treatment response rate. DAC 15 mg/m 2 /8 h for 3 days every 42 days was inferior to the other regimens, which is consistent with a previous report demonstrating that it was less effective than DAC 20×5 every 28 days for all-risk MDS [ 21 ]. However, among 28-day regimens, AZA 75×7 and DAC 20×5 had the highest response rates, although a statistical analysis was not possible because of the high heterogeneity, or did not show statistically significant differences because of the limited data.…”
Section: Discussionsupporting
confidence: 91%
“…The patients in our study were mainly ESA/EPO-refractory and transfusion-dependent, and could have a very poor outcome if left untreated. Based on the clinical characteristics of our cohort, HMAs could benefit relatively high-risk patients (int-1–risk) within the LR-MDS group, at least for the short term, as suggested by other studies [ 20 , 21 ]. However, because of the paucity of studies and lack of detailed information, we were unable to determine which WHO/FAB classifications would benefit most from HMAs TI rate is an important parameter for LR-MDS patients as it reflects patients’ quality of life and risk of leukemic transformation and mortality.…”
Section: Discussionsupporting
confidence: 53%
“…A meta-analysis suggested that decitabine at 100 mg/m 2 /course dosing regimen had a greater clinical benefit in treating MDS than decitabine at 60 to 75 mg/m 2 /course and 135 mg/m 2 /course regimens. [ 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dosage: a higher risk of infectious complications was observed in patients treated with azacitidine 75 mg/m 2 for 7 days, than in those receiving 5 days of therapy [39,40]. This association was not observed in other experiences [23,26] The rate of infections in decitabine-treated patients did not decrease when reducing the decitabine dose [46]. Cycles: the rate of infectious events was higher in the first 3 azacitidine cycles and tended to decline with sequential cycles [7,23,25,26,41,42].…”
Section: Hypomethylating Agents Treatmentmentioning
confidence: 95%
“…Infection-related deaths occurred only in Gram-negative events (13%); infection-related complications occurred during any cycle of therapy, and the incidence did not decrease during later cycles [22]. A recent meta-analysis has indicated that the rate of infections in decitabine-treated patients did not decrease when reducing the decitabine dose [46].…”
Section: Epidemiology Of Infections In Patients With Mds Receiving Current Therapymentioning
confidence: 99%